Analisis Kesalahan Siswa dalam Menyelesaikan Soal Eksponen - Rindu, Oyafianus; Fernandez, Aloysius Joakim (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to analyze students’ errors in solving exponent problems in terms of conceptual understanding, skills, and problem-solving aspects. The research method employed was descriptive qualitative with two students of SMA St. Arnoldus Janssen Kupang as subjects, selected based on test results and teacher recommendations. The research instruments consisted of written tests and interviews, while the data analysis techniques included data reduction, data presentation, and conclusion drawing. The results showed that the first subject made errors in the problem-solving indicator on question number 2 and errors in all indicators on question number 3. Meanwhile, the second subject made errors in conceptual understanding and skills on question number 1 and complete errors on question number 3. Overall, the most dominant errors committed by students were in conceptual understanding, skills, and problem-solving, particularly in applying the properties of exponents. These findings provide important implications for teachers to emphasize concept-based learning and provide varied practice problems to improve students’ skills and problem-solving abilities.